(untitled) (Journal of Intellectual Property Rights (JIPR), 2025)
The potentially disruptive interaction between Artificial Intelligence (AI) and creative Intellectual Property Rights (IPRs) is one of the major challenges of the 21st century as AI systems are being increasingly utilized to generate creative works. This article addresses these questions through the lens of copyrightability of works created by AIs as it relates to originality, authorship, and ownership. The paper addresses recent debates about whether current copyright frameworks could be adapted to accommodate AI-generated content and outlines practices around the world. It also explores the crucial role of human intervention in AI output, arguing whether such collaborations deserve co-authorship credit. The paper ends with suggestions to amend the laws which apply in these circumstances, or to create a new legal framework to resolve these issues.